Environmental Degradation as a Deviation of Tauhid: Analysis of the Film WALL-E from the Perspective of Mawil Izzi Dien - V Nazia; M Putra; D Firdaus; M Iswara; M Triana (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
The global environmental crisis is not merely a technical issue but reflects a deeper moral and spiritual crisis within humanity. This research analyzes the representation of environmental degradation in the film WALL-E through the lens of Islamic Environmental Ethics as proposed by Mawil Izzi Dien. Using a qualitative textual analysis method, the study explores how the film’s depiction of a waste-covered Earth and consumerist human lifestyle mirrors the Quranic concept of fasad (destruction). The findings indicate that the environmental collapse portrayed in the film is a systemic breach of mizan (balance) and a failure of humans to fulfill their role as khalifah (stewards). Ultimately, the research argues that environmental crises are manifestations of a deviation from the principle of Tauhid (the Oneness of God), where humanity’s spiritual disconnect leads to the exploitation of nature. The study concludes that addressing ecological issues requires a reconstruction of spiritual awareness rooted in theological responsibility.